Conocimientos, actitudes y prácticas en salud bucal, medios de comunicación y mercadeo social en escolares de 7 a 12 años de una institución de Medellín (2005)
ABSTRACT: One of the most affected groups by oral health problems is the paediatric population, therefore the present research was undertaken, mainly focusing in the knowledge, attitudes, practices and some expectations in oral health, mass media, and social marketing in children of 7 to 12 years of age from the Rafael Uribe Uribe school in Medellín city. A structured interview format was designed with 31 questions that enquired about this subject, and then an analysis of variables was made by establishing analysis categories within the objectives of the study. The results showed that the students have some knowledge on the relationship of the dentist’s role as a integral person on the promotion of oral health, prevention and rehabilitation; some previous knowledge and association with dental caries, a very positive perception about the dentist consultation and good self-esteem of their teeth. In relation to their practices; the children have received instruction in oral health by the dentistry personal as well as from their family and they utilize the basic elements for their hygiene. Also, they recognize informative and/or communicative elements in the dental office and in a lower rate, in the educational institution; they think it is important to give messages in oral health through the dialogue with the dentist and they declare certain inclinations and preferences with mass media and publicity in the radio, television and others. This information permitted the design of strategies for campaigns on oral health promotion, where other disciplines were involved such as communication, psychology and social marketing as alternatives to contribute to the oral health positioning in the population studied. In addition, a framework of reference for future intervention projects in specific populations is constituted involving a high communicative and educational component.